2009
DOI: 10.2478/s11532-009-0041-z
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of horseradish peroxidase by covalent conjugation with dextran aldehyde against temperature and pH changes

Abstract: Stabilization of Horseradish Peroxidase (HRP; EC 1.11.1.7) against temperature and pH via the formation of the conjugates obtained by multipoint covalent bonding of dextran aldehyde (DA) to the enzyme were studied. Hence, three different molar weighted dextrans (17.5 kD, 75 kD, 188 kD) were covalently bonded to purified enzyme with different molar ratios (nHRP/nDA 20/1, 10/1, 1/1, 1/5, 1/10, 1/15, 1/20). The thermal stabilities of the obtained conjugates were evaluated with the activities determined at differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…As the temperature is increased from 30°C to 70°C, at pH 7, a slow decrease in the rate was observed. The reason may be attributed to the fact that the activity of purified HRP enzyme decreases at temperatures above 30°C, as determined in our previous study [31]. As clearly shown in Fig.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…As the temperature is increased from 30°C to 70°C, at pH 7, a slow decrease in the rate was observed. The reason may be attributed to the fact that the activity of purified HRP enzyme decreases at temperatures above 30°C, as determined in our previous study [31]. As clearly shown in Fig.…”
Section: Resultsmentioning
confidence: 82%
“…The fractions containing HRP activity were collected and concentrated in ultrafiltration cell with Regenerated Cellulose membrane (Dia 25 mm, Mw 10.000) by washing 2 times with distilled water and 2 times with 0.01 M phosphate buffer, pH 7. RZ value (A 460 /A 280 ) of the enzyme was determined as 2.24 [31]. The analytical determination was carried out in duplicate, and the average was used as a datumpoint.…”
Section: Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption is supported by different studies trying to enhance the temperature stability of HRP, e.g., by modification of amino acid residues, [73] or conjugation with, e.g., dextran. [74]…”
Section: Passive Release Of Strephrpmentioning
confidence: 99%
“…The literature reported that by obtaining the stable horseradish peroxidase-dextran aldehyde conjugates can improve the stability of HRP against the inverse environment such as high temperature. Multipoint covalent bonding of dextran to horseradish peroxidase caused the formation of a conjugate whose thermal stability was highest at pH 7 and the molar ratios of HRP and dextrans provided to obtain the conjugate was 1/10 [10] . However, these methods still have limitations in practical applications such as poor resistance activity, and large amount of protective agent.…”
Section: International Conference On Engineering and Technology Innovmentioning
confidence: 99%